2018
DOI: 10.1007/978-3-319-65798-1_59
|View full text |Cite
|
Sign up to set email alerts
|

Systolic and Diastolic Regulation of the Cerebral Pressure-Flow Relationship Differentially Affected by Acute Sport-Related Concussion

Abstract: Impairments in autoregulatory capacity, observed for a transient period following SRC that persist beyond symptom resolution and clinical recovery, appear to be differentially affected across the cardiac cycle. Similar patterns of impairment were observed for systolic and diastolic phases (response latency); however, normalized gain (response magnitude) impairments were identified only in diastole. These findings may explain the increased cerebral vulnerability as well as exercise-induced symptom exacerbation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…Ogoh and coworkers (Ogoh, Dalsgaard, et al, ; Ogoh, Fisher, et al, ) found diastolic dynamic CA was impaired during exercise and acute recovery (10 min) within the LF band, despite the 5‐min averaged diastolic MCA blood velocity appearing to be well maintained. These results are similar to those previously reported in athletes who have sustained an acute sports‐related concussion (Wright, Smirl, Bryk, & Donkelaar, ). Both MCA and PCA blood velocities have previously been shown to increase following moderate exercise, likely influenced by the elevated P ET CO2 associated with subanaerobic threshold exercise.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Ogoh and coworkers (Ogoh, Dalsgaard, et al, ; Ogoh, Fisher, et al, ) found diastolic dynamic CA was impaired during exercise and acute recovery (10 min) within the LF band, despite the 5‐min averaged diastolic MCA blood velocity appearing to be well maintained. These results are similar to those previously reported in athletes who have sustained an acute sports‐related concussion (Wright, Smirl, Bryk, & Donkelaar, ). Both MCA and PCA blood velocities have previously been shown to increase following moderate exercise, likely influenced by the elevated P ET CO2 associated with subanaerobic threshold exercise.…”
Section: Discussionsupporting
confidence: 91%
“…To prevent BP surges from causing irreversible damage in the cerebrovasculature, CA is thought to act as a buffer to protect the brain from cerebral hyperperfusion (Ogoh, Fisher, et al, ; Smirl et al, ; Wright, Smirl, Bryk, & Donkelaar, ). Ogoh and coworkers (Ogoh, Dalsgaard, et al, ; Ogoh, Fisher, et al, ) found diastolic dynamic CA was impaired during exercise and acute recovery (10 min) within the LF band, despite the 5‐min averaged diastolic MCA blood velocity appearing to be well maintained.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main drawback of SSM is the difficulty of their use in incapacitated subjects, people with mobility issues or those with cognitive impairment (Van Beek et al, 2008;Smirl et al, 2015). Despite the difficulty of applying SSM in some clinical conditions, a number of previous studies have already demonstrated its feasibility (Claassen, Diaz-Arrastia, et al, 2009;Lewis et al, 2019;Smirl et al, 2014;Wright, Smirl, Bryk, & van Donkelaar, 2018).…”
mentioning
confidence: 99%